Pelatihan Maintenance Ringan Kendaraan Roda Empat bagi Masyarakat Bambu Apus - Giyanto .; Thohirudin .; Sugiono . (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2026)
Community dependence on automotive workshops to handle minor problems in four-wheeled vehicles, particularly car air conditioning (AC) systems, often leads to relatively high maintenance costs and delays in addressing early-stage damage. Preliminary observations in Bambu Apus Village, Pamulang, revealed that most residents own four-wheeled vehicles but have limited knowledge and skills in performing light maintenance independently. Common problems include reduced cooling performance, unpleasant odors, and decreased driving comfort, which could actually be prevented through simple and proper maintenance procedures. This Community Service Program aims to improve community understanding and practical skills in performing light maintenance of four-wheeled vehicle AC systems independently, safely, and correctly, thereby reducing dependence on workshops and improving vehicle comfort and safety. The program applied a participatory training method based on the autonomous maintenance approach. Activities were conducted through several stages, including a preliminary survey, material socialization, technical demonstrations, and hands-on practice. Program effectiveness was evaluated using pre-test and post-test questionnaires, as well as direct observation of participants’ practical skills during field practice sessions. The results indicate a significant improvement in participants’ understanding of the main components and working principles of car AC systems, recognition of early signs of minor damage, and ability to perform basic inspections and light maintenance independently. Participants also demonstrated increased awareness of occupational safety and health (OSH) aspects during vehicle maintenance activities. This program contributes to strengthening community self-reliance in vehicle maintenance and provides a sustainable technical training model at the community level.